2022
DOI: 10.1371/journal.pone.0272372
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula oxygen therapy for admitted COPD-patients. A retrospective cohort study

Abstract: Background The use of High-flow nasal cannula (HFNC) is increasing in admitted COPD-patients and could provide a step in between non-invasive ventilation (NIV) and standard oxygen supply. Recent studies demonstrated that HFNC is capable of facilitating secretion removal and reduce the work of breathing. Therefore, it might be of advantage in the treatment of acute exacerbations of COPD (AECOPD). No randomized trials have assessed this for admitted COPD-patients on a regular ward and only limited data from non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In addition, 32% of patients in HFNC group switched to NIV by 6 hours, and 57.5% received NIV during hospitalization [ 17 ]. In a more recent large retrospective study of 173 hospitalized COPD patients receiving HFNC, 68 patients (39%) experienced HFNC failure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 32% of patients in HFNC group switched to NIV by 6 hours, and 57.5% received NIV during hospitalization [ 17 ]. In a more recent large retrospective study of 173 hospitalized COPD patients receiving HFNC, 68 patients (39%) experienced HFNC failure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that elevated NT-proBNP level is associated with worse in-hospital outcomes and is a reliable predictive biomarker of poor prognosis in patients with AECOPD [ 36 , 37 ]. In a more recent study, Veenstra and colleagues found a significant association between cardiac (myocardial infarction, heart failure, or arrhythmia) (OR = 0.435, p = 0.013) and vascular (hypertension and peripheral arterial disease) (OR = 0.493, p = 0.035) comorbidity and a lower likelihood of HFNC success in AECOPD patients [ 29 ]. In the present study, our results further indicate that the NT-proBNP level upon admission might be an important factor for HFNC failure in AECOPD patients with respiratory acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…But a few points worth mentioning would be that high-flow methods were non-inferior to NIV in decreasing PaCO 2 within two hours of treatment [ 96 ], and the use of high-flow methods in AECOPD with sputum stasis showed good tolerance among these patients [ 97 ].…”
Section: Reviewmentioning
confidence: 99%
“…The flow rates for the devices used for oxygen delivery are mentioned in Based on the data in Table 8, we can see that NIV and high-flow oxygen delivery methods do not show significant differences in the outcome of treating AECOPD patients, especially the criteria for intubation. But a few points worth mentioning would be that high-flow methods were non-inferior to NIV in decreasing PaCO 2 within two hours of treatment [96], and the use of high-flow methods in AECOPD with sputum stasis showed good tolerance among these patients [97].…”
Section: Oxygen Prescriptionmentioning
confidence: 99%
“…F rat et al [ 33 ] showed that high flow nasal oxygen (HFNO) was non-inferior to standard oxygen therapy or NIV in preventing intubation with non-hypercapnic acute hypoxic respiratory failure. The use of HFNO is increasing in admitted COPD patients with acute exacerbations and could help with secretion removal and reduce the work of breathing especially in patients who do not require NIV management as part of their treatment, but have severe hypoxaemic respiratory failure [ 34 ]. There are a number of proposed benefits for this specific subgroup of patients, who have a significant degree of mucus burden but do not have severe acidotic respiratory failure.…”
Section: Oxygen Therapy and Nivmentioning
confidence: 99%